A review of Bioinformatics training applied to research in Molecular Medicine, Agriculture and Biodiversity in Costa Rica and Central America - Orozco Solano, Allan (2013)
artículo -- Universidad de Costa Rica, Escuela de Medicina. 2013. Este documento no es público debido a limitaciones de derechos de autor.